Association of postnatal severe acute malnutrition with pancreatic exocrine and endocrine function in children and adults: a systematic review. Issue 4 (28th February 2023) - Ferdous, Farzana; Filteau, Suzanne; Schwartz, Nanna Buhl; Gumede-Moyo, Sehlulekile; Cox, Sharon Elizabeth
Abstract: Severe acute malnutrition may lead both concurrently and subsequently to malabsorption and impaired glucose metabolism from pancreatic dysfunction. We conducted a systematic review to investigate the associations of current and prior postnatal wasting malnutrition with pancreatic endocrine and exocrine functions in humans. We searched PubMed, Google Scholar, Web of Science and reference lists of retrieved articles, limited to articles in English published before 1 February 2022. We included sixty-eight articles, mostly cross-sectional or cohort studies from twenty-nine countries including 592 530 participants, of which 325 998 were from a single study. Many were small clinical studies from decades ago and rated poor quality. Exocrine pancreas function, indicated by duodenal fluid or serum enzymes, or faecal elastase, was generally impaired in malnutrition. Insulin production was usually low in malnourished children and adults. Glucose disappearance during oral and intravenous glucose tolerance tests was variable. Upon treatment of malnutrition, most abnormalities improved but frequently not to control levels. Famine survivors studied decades later showed ongoing impaired glucose tolerance with some evidence of sex differences. The similar findings from anorexia nervosa, famine survivors and poverty- or infection-associated malnutrition in low- and middle-income countries (LMIC) lend credence to results being due to malnutrition itself. Research using large, well-documented cohorts and considering sexes separately, is needed to improve prevention and treatment of exocrine and endocrine pancreas abnormalities in LMIC with a high burden of malnutrition and diabetes.